Teacher Talk in Classroom Interaction: A Study at an English Department in Indonesia - Ryan Rayhana Sofyan; Murni Mahmud (ELT Worldwide: Journal of English Language Teaching, 2014)
The research aims at analyzing teacher talk in classroom interaction based on Foreign Language Interaction Analysis (FLINT) system in speaking classroom of English department of Language and Literature Faculty of State University of Makassar. The method used in this research was a descriptive method. The instruments were FLINT system. The participants of the research were the lecturer and students of a speaking class during the second semester of academic year 2011/2012 at English Department of Language and Literature Faculty of State University of Makassar. The results of the research are: teacher talk of giving praises and encouragement is approximately less, the asking questions category dominate the teacher talk category, which means it is in the beneficial function. The lecturer asked the questions to the students and the students responded it well by speaking eagerly. The utterances of giving direction occurred in relatively short times. While in student talk, there are students’ problems and difficulties in speaking. The extracts of student talk in classroom interaction revealed the students problems such as the lack of vocabulary, anxiety, inability to form ideas in English language form, and grammar error. The teacher talk frequency was still excessive, but the lecturer made group and pair discussions to balance the effective talk for students in student-student interaction. Keywords: Classroom, interaction, FLINT, Speaking